NON-SYMBIOTIC NITROGEN FIXATION, NET NITROGEN MINERALIZATION AND DENITRIFICATION IN EVERGREEN FORESTS OF CHILOÉ ISLAND, CHILE: A COMPARISON WITH OTHER TEMPERATE FORESTS FIJACION NO-SIMBIOTICA, MINERALIZACION NETA DEL NITROGENO Y DESNITRIFICACION EN BOSQUES SIEMPREVERDES DE CHILOE, CHILE: UNA COMPARACION CON OTROS BOSQUES TEMPLADOS - C.A. Pérez (Universidad de Concepción, 2003)
Temperate forests in southern Chile offer unique opportunities for studying biogeochemical cycles in the absence of industrial air pollution. Here we compare three important fluxes of the nitrogen (N) cycle in temperate forests of southern Chile, non-symbiotic N fixation, net N mineralization and denitrification, with data from northern temperate forests more affected by air pollution. We studied five evergreen, old-growth forests and one second-growth forest in Chiloé Island, southern Chile. Non-symbiotic N fixation in the litter layer, mineral soil and coarse woody debris was estimated by the acetylene reduction technique. In situ net-N mineralization in the upper mineral soil layer was assessed by the buried bag method. Denitrification rates of mineral soil were assessed by the acetylene inhibition essay in intact soil cores. Results show that in some southern temperate forests a greater proportion of the ecosystem N-fixation occurs in the litter layer (0.23-2.26 kg N ha-1 year-1) and coarse woody debris (1.31-1.34 kg N ha-1 year-1). In contrast, the highest N fixation rates in northern temperate forests occur in mineral soil. Rates of both N mineralization and denitrification were considerably lower in Chiloé forests than in northern temperate forests, which are subject to higher N deposition. These findings suggest that southern temperate forests exert a stronger biotic control on N cycling than their northern counterparts Los bosques templados de Chile ofrecen un escenario único para estudiar los ciclos biogeoquímicos debido a su condición libre de contaminación industrial. Comparamos tres flujos importantes del ciclo del nitrógeno (N), tales como fijación no simbiótica, mineralización neta y desnitrificación, en bosques del sur de Chile con datos de bosques templados del hemisferio norte sujetos a contaminación. Estudiamos cinco bosques siempreverdes maduros y uno secundario en la Isla de Chiloé. La fijación no simbiótica del nitrógeno en la hojarasca, el suelo mineral y desechos leñosos gruesos, se estimó mediante el método de reducción de acetileno. La tasa neta de mineralización del suelo superficial se estimó con el método de la bolsa enterrada. La tasa de desnitrificación se estimó mediante el ensayo de inhibición con acetileno en muestras de suelo intactas. Los resultados muestran que en algunos bosques templados chilenos una mayor proporción de la fijación no simbiótica del N ocurre en la hojarasca (0,23-2,26 kg N ha-1 año-1) y en los desechos leñosos gruesos (1,31-1,34 kg N ha-1 año-1). En cambio, las mayores tasas de fijación de N en los bosques templados del hemisferio norte han sido encontradas en el suelo mineral. Los bosques siempreverdes de Chiloé presentaron tasas de mineralización neta y desnitrificación considerablemente menores que los bosques templados del hemisferio norte, tanto siempreverdes como deciduos. Interpretamos estos resultados como indicadores que los bosques templados del hemisferio sur poseen un control más eficiente de la circulación interna del N que su contra parte del hemisferio norte